PENGARUH DUKUNGAN SOSIAL ORANG TUA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SMAN 15 PADANG (STUDI TERHADAP PESERTA DIDIK FASE E DARI KELUARGA BROKEN HOME) - Zakiyah Fauziyah; Zulkifli; Rahmawati Wae (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by parents who pay less attention to students, parents who do not pay attention to students related to assignments given by teachers, there are parents who are less concerned with student learning outcomes. This study aims to describe the influence of parental social support on student learning motivation from broken home families at SMAN 15 Padang. The method used is descriptive quantitative with a correlational approach. The research population is phase E students from broken home families totaling 33 people, with a total sampling technique. The instrument is a questionnaire and data are analyzed using a simple linear correlation technique. The results show that: (1) parental social support is in the low category, (2) student learning motivation is in the low category, and (3) there is a significant influence between parental social support on student learning motivation. These findings provide recommendations for BK teachers and parents to increase their active role in the child's learning process.